Degradation of polycrystalline zeolitic imidazolate framework membrane under reactive plasma conditions - Hyungjoon Ji; Wooyoung Choi; Eunji Choi; Yunseong Ji; Minsu Kim; Hwan-Jin Jeon; Dae Woo Kim (Journal of Membrane Science Letters)
Polycrystalline layers of metal-organic frameworks (MOFs) are effective for fabricating high-performance membranes, particularly for gas separation. However, the chemical degradation of these polycrystalline layers has not been extensively studied, though it is reasonable to anticipate severe degradation under harsh conditions. Accordingly, we investigated the mechanisms of morphological deformation and chemical structure changes in zeolite imidazolate framework (ZIF)-8 films under highly reactive conditions using plasma. ZIF-8 was selectively chosen among various MOFs due to its widespread use in gas separation applications and its relatively stable chemical bonds. The plasma generated various reactive species, such as ions and radicals, to accelerate the degradation of the ZIF-8 layer. We observed that reactive Ar ions preferentially etch Zn over C, and fluorine-containing radicals chemically react with Zn to form covalent bonds. Notably, we found that the degradation of the polycrystalline layer initially begins at the grain boundaries. However, as defects form on the grain surfaces, the degradation progresses more extensively within the grains than at the grain boundaries.